2022
DOI: 10.3389/fpubh.2022.929043
|View full text |Cite
|
Sign up to set email alerts
|

Actively incorporating lifestyle modifications into daily life: The key to adherence in a lifestyle intervention programme for metabolic syndrome

Abstract: IntroductionLifestyle modifications are the first-line interventions for metabolic syndrome (MetS) management. The effectiveness of lifestyle interventions depends mostly on participants' adherence to the interventions. The current study was to explore the experiences of MetS patients in attending lifestyle intervention program (LIP) and the factors that influenced their adherence to the interventions.MethodsA descriptive qualitative study was designed following the COREQ guideline. Face-to-face semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The concept of individualization refers to creating intervention content based on an individual's specific characteristics, such as existing behaviors, stages of behavior change, preferences, and barriers [23]. A previous study confirmed that individualized lifestyle education helped patients with MetS incorporate lifestyle interventions into their daily lives [24]. According to a meta-analysis, individualized interventions may be an effective approach for adults to reduce MetS parameters [23], which could be attributed to the fact that they meet patients' individualized needs and provide tailored measures, considering that every patient is unique and has distinct requirements.…”
Section: The Need For Individualized Mhealth-based Interventionmentioning
confidence: 99%
“…The concept of individualization refers to creating intervention content based on an individual's specific characteristics, such as existing behaviors, stages of behavior change, preferences, and barriers [23]. A previous study confirmed that individualized lifestyle education helped patients with MetS incorporate lifestyle interventions into their daily lives [24]. According to a meta-analysis, individualized interventions may be an effective approach for adults to reduce MetS parameters [23], which could be attributed to the fact that they meet patients' individualized needs and provide tailored measures, considering that every patient is unique and has distinct requirements.…”
Section: The Need For Individualized Mhealth-based Interventionmentioning
confidence: 99%